Self-esteem and its associated demographic factors among undergraduate nursing students at a tertiary institution in Southwestern Uganda: A cross-sectional study. - Atuhaire, Andrew; Kasasa, Doris Babirye; Atuhaire, Catherine; Niyonzima, Vallence; Luwaga, Rachel (Student's Journal of Health Research Africa, 2025)
Introduction Self-esteem refers to one’s positive or negative attitude towards oneself and the evaluation of one’s thoughts and feelings overall about oneself. It is a vital element in a person’s life as it affects the overall human behaviours and relationships. The level of self-esteem has an impact on the way one accepts responsibilities, their communication skills, and the way one cooperates with others, human response to stressful life events, and how to deal with positive and negative emotions. Purpose: To assess levels of self-esteem and demographic factors associated with self-esteem levels among undergraduate nursing students of Mbarara University of Science and Technology. Methodology The study used a cross-sectional study design and recruited 139 students who are undergraduate nurses at Mbarara University of Science and Technology. The self-esteem of the participants was measured using the Rosenberg Self-esteem Scale (RSES), and data were analyzed using SPSS version 23. Results 59.70% of the participants had moderate levels of self-esteem, 40.3% had low self-esteem, and no one had high self-esteem. Of all the assessed demographic factors, age, sex, year of study, program of study, marital status, sponsorship program, and religion, year of study was the only factor significantly associated with levels of self-esteem. Conclusion There are no undergraduate nursing students with high self-esteem at Mbarara University of Science and Technology. Recommendations Additional research on self-esteem and associated demographic factors ought to be done using much larger populations so as to have enough data to make adequate statistical analysis, probably a study involving nursing students from different nursing institutions all at once. A qualitative study, as well as to further describe the relation between self-esteem and associated demographic factors, is key in further understanding this concept.